The Whereabouts Clock: Early Testing of a Situated Awareness Device - Sellen, Abigail; Eardley, Rachel; Izadi, Shahram; Harper, Richard (CHI '06 Extended Abstracts on Human Factors in Computing Systems, 2006)
We describe the initial deployment of a prototype device to support awareness of people's location and activities in an office environment. This is a first step toward the design and testing of a related device for the home. Findings from this workplace trial show its value in helping people have a virtual presence, in locating people, and in fostering a sense of group belonging. However, the results also suggest how the design could be made more flexible and expressive which we will explore in the upcoming home trial.